The significance of psychological preparation in martial arts - Đurović Dušanka; Sokić Jelena (University Educons, Faculty of Sports and Tourism, Novi Sad, 2018)
Overview of psychological research in the field of sport consistently shows the importance and effectiveness of psychological preparation in improving sports performance. The results of investigations of psychological factors and their success in martial arts indicate the most significant psychological skills that one needs to develop and that contribute to success: concentration and focused attention, self-confidence, relaxation, regulation of excitement and tension, control over anxiety, visualization and self-talk. Individual approach to the process of learning the psychological techniques and accommodation to personalized features of athletes have proven to be more effective than a group approach.